Hubungan Kompetensi Keselamatan Pasien dengan Perilaku Keselamatan Pada Perawat di RSU X Tangerang - Lusianah, Lusianah; Kurniawati, Any (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
In health care settings, patient safety is a major concern. The emergence of diseases, the aggressiveness of germs, and environmental changes force nurses to improve their patient protection skills. The phenomena at RSU X suggests dangerous behavior in carrying out work when debriefing and monitoring about impacted person protection have been completed robotically. This suggests that nurses' safety behavior is still insufficient. The purpose of this study is to determine the connection between nurses' skill in patient protection and their safe behavior in RSU X. This study's design employs a cross-sectional approach to corroborate data. The examination was carried out at RSU X in Tangerang Banten. 184 nurses participated in this study as respondents. With a p value of 0.0001, the results suggested a strong relationship between skill level and patient protective behavior. It can be said that nurses at RSU X have a relationship between their competency level and patient safety practices.